Evaluation of sunflower germplasm for resistance against leafhopper, Amrasca biguttula biguttula (Ishida): Evaluation of sunflower germplasm for resistance against leafhopper, Amrasca biguttula biguttula (Ishida) - TABASSUM FATIMA; G SRIDEVI; P S SRINIVAS; K V RADHAKRISHNA; BHARATI BHAT (Journal of Oilseeds Research, 2020)
Sixty accessions of sunflower were screened under natural infestation in rabi, 2017-18 for their reaction toleafhopper (Amrasca biguttula biguttula Ishida). Out of 60 germplasm lines screened, 42 lines were recorded thelowest injury grading of I. Two accessions GMU-339 and TSG-349 were found promising with the lowest leafhopperpopulation and the lowest injury grade of I.